2006
DOI: 10.1007/s10620-006-3191-2
|View full text |Cite
|
Sign up to set email alerts
|

An Inverse Correlation of Human Peripheral Blood Regulatory T Cell Frequency with the Disease Activity of Ulcerative Colitis

Abstract: Evidence suggests that CD4+CD25+ regulatory T cells play a crucial role in the suppression of intestinal inflammation. However, their role in the suppression of inflammatory bowel disease has not yet been addressed. We examined the proportion of regulatory T cells in inflammatory bowel disease. First, we isolated CD4+CD45RO+CD25+ T cells from the peripheral blood of healthy persons and showed that these cells suppressed T cell proliferation profoundly and expressed FoxP3 abundantly, revealing that they are reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
61
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(71 citation statements)
references
References 37 publications
8
61
1
1
Order By: Relevance
“…T reg cells have been found in human lamina propria tissue in both inflamed and healthy states (52). In addition, peripheral T reg cells are significantly lower in number from patients with active ulcerative colitis (UC), a form of IBD, than those from healthy patients (53). In accordance with this, T reg cells are essential for prevention and cure of experimental colitis in murine models (54).…”
Section: Discussionmentioning
confidence: 91%
“…T reg cells have been found in human lamina propria tissue in both inflamed and healthy states (52). In addition, peripheral T reg cells are significantly lower in number from patients with active ulcerative colitis (UC), a form of IBD, than those from healthy patients (53). In accordance with this, T reg cells are essential for prevention and cure of experimental colitis in murine models (54).…”
Section: Discussionmentioning
confidence: 91%
“…Early studies found that patients with CD or UC have decreased numbers of peripheral suppressive CD4 + CD45RO + CD25 + FOXP3 + Treg cells during active disease, suggesting that the severity of disease is inversely correlated with the frequency of peripheral Treg cells. [12][13][14][15] In contrast, several studies have found that the lamina propria, mesenteric lymph nodes and intestinal inflamed mucosa of patients with either CD or UC actually contain increased numbers of Treg cells compared with healthy controls. 5,13,15,16 These data are consistent with findings in other gut-inflammatory conditions, such as diverticulitis, pseudomembranous colitis and cytomegalovirus-induced colitis, which show a similar correlation between an increase in FOXP3 + Treg-cell numbers and disease severity.…”
Section: M M U N O L O G Y R E V I E W a R T I C L Ementioning
confidence: 99%
“…6,8 Also in humans, immune dysregulation polyendocrinopathy enteropathy X-linked syndrome (IPEX) is an auto-immune disease developed from a deficiency of T regs. [8][9][10][11] These observations indicate that T regs play important roles in immunological homeostasis. Although the mechanisms of suppression by T regs are still unclear, it has been reported that T regs can inhibit the function of effector T cells directly by cell to cell contact or indirectly via the secretion of immune-suppressive cytokines.…”
mentioning
confidence: 93%